EFFECT OF MODIFIED STARCH ON THE SHELF LIFE OF FROZEN FISH KAMABOKO WITH PREPARED SPINACH - Desai, A. S.; Joshi, V. R.; Pagarkar, A. U. (Journal of Indian Fisheries Association, 2015)
Fish kamaboko ·with spinach was prepared by mixing fish kamahoko vdth spinach prepared with different combinations of ordinary starch (OS) and modified starch (MS), viz., 40:60, 50:50, 60:40, 1 00°/.) MS and I 00°/o OS. The Oil oc . products were frozen at -4 C and stored at -20 , and subJected to biochemical (peroxide value, total titratable acidity, pH and moisture) organoleptic (appearance, taste and colour), microbiological (total plate count) and physical (folding and expressible water) tests at monthly intervals. Among the different combinations tried, it was observed that fish kamaboko with spinach prepared with 50:50 and 60:40 combinations of OS and S cou be stored for six months at-20uC. Keywords: lVlodif1ed starch, ordinary starch, f1sh kamaboko, spinach product